Histomorphometry of tissue repair after use of formulations based on extracts of Piptadenia gonoacantha (Mart.) J. F. Macbr. - Ribeiro, Cassia Gondim Pereira; Amaro, Marilane de Oliveira Fani; Frescura, Lucas Mironuk; Avila, Mariane Borges Rodrigues de; Rosa, Marcelo Barcellos da; Carvalho, Camilo Amaro de; Xavier, Juliana Cantele (Archives of Veterinary Science, 2024)
Piptadenia gonoacantha is a tree species with several biological properties. The objective of this study was to evaluate the action of two pharmaceutical formulations, ointment and balm, containing Piptadenia gonoacantha extract, on the healing of wounds made in 45-day-old male mice. The animals were randomly grouped and 3 treatments with 6 repetitions were performed: an ointment containing the extract; balm containing the extract and silver sulfadiazine was used as the positive control. Tissue samples were collected on the 4th and 8th days. Treatment began immediately after the injury, and the treatments were applied once a day throughout the experiment. Treatment with the balm formulations on day 4 and the ointment on day 8 had better wound area regression rates compared to the control group, 45.4% and 81.6%, respectively. The balm and ointment treatments provided a reduction in vascularity indicating a reduction in the inflammatory process, initiating the proliferative phase in the scar tissue. These data were supported by the analysis of collagen synthesis. The results pointed out the efficacy of balm and ointment formulations concerning sulfadiazine. Therefore, the balm formulation is indicated for the beginning of the treatment, while the ointment formulation is indicated for continuation and end of treatment.